From Heritage to Terrorism : Regulating Tourism in an Age of Uncertainty. - Simpson, Brian (Taylor & Francis, 2010)
Examines the law and its role in shaping and defining tourism and the tourist experience. Using a range of legal documents and other materials from a variety of disciplines, this title surveys how the underlying values of tourism often conflict with a concern for human rights, cultural heritage and sustainable environments.